Pengembangan Sistem Informasi Manajemen Klinik Gigi Terintegrasi Berbasis Web untuk Optimalisasi Pelayanan dan Rekam Medis Pasien di Klinik Lala Dentist Jember - Tegar Wahyu Yudha Pratama; Nur Malika Jamil; Anggi Maulidya; Assyifa Itsnainia Mustika (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2026)
Dental health services in Indonesia still face various obstacles, particularly in terms of access, service delays, and an unintegrated medical record system. Lala Dentist Jember Clinic, which serves more than 300 patients per month, also experiences similar problems, because the registration process, recording medical records, reporting, and payments are still done manually. This results in data duplication, service delays, recording errors, and difficulties tracking patient treatment histories. The purpose of this study was to identify the needs of a management information system at Lala Dentist Jember Clinic, design an integrated system according to RME standards with interactive administration and odontogram features, and test its feasibility and effectiveness. The research method used a Research and Development (R&D) approach with a Waterfall System Development Life Cycle (SDLC) model using the PHP/Laravel and MySQL frameworks. The results of this study are an integrated information system according to RME standards with interactive administration and odontogram features that can help the effectiveness and productivity of the clinic's service process, but also contribute to the digital transformation of health in Indonesia by strengthening patient data integration and improving medical information security. The study concluded that the system simplifies registration, queue management, electronic medical record keeping, and the presentation of clinical reports more quickly and accurately. The web-based system also supports real-time data access and minimizes administrative errors, thus optimizing services and improving the quality of clinical management.